Modeling the Sequential Pattern Variability of the Electromotor Command System of Pulse Electric Fish - Lareo, Angel; Varona, Pablo; Rodriguez, Francisco B. (Frontiers in Neuroinformatics, 2022)
Mormyridae, a family of weakly electric fish, use electric pulses for communication and for extracting information from the environment (active electroreception). The electromotor system controls the timing of pulse generation. Ethological studies have described several sequences of pulse intervals (SPIs) related to distinct behaviors (e.g., mating or exploratory behaviors). Accelerations, scallops, rasps, and cessations are four different SPI patterns reported in these fish, each showing characteristic stereotyped temporal structures. This paper presents a computational model of the electromotor command circuit that reproduces {a whole set of SPI patterns keeping the same internal network configuration. The topology of the model is based on a simplified representation of the network with four neuron clusters (nuclei). An initial configuration was built to reproduce nucleus characteristics and network topology as described by detailed morphological and electrophysiological studies. Then, a methodology based in a genetic algorithm (GA) was developed and applied to tune the model connectivity parameters to automatically reproduce a whole set of patterns recorded from freely-behaving Gnathonemus petersii specimens. Robustness analyses to input variability were performed to discard overfitting and assess validity. Results show that the set of SPI patterns are consistently reproduced \added{reaching a dynamic balance between synaptic properties in the network}. This model can be used as a tool to test novel hypotheses regarding temporal structure in electrogeneration. Beyond the electromotor model itself, the proposed methodology can be adapted to fit models of other biological networks that also exhibit sequential patterns.